2017
DOI: 10.1016/j.clgc.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Clinical Trial of TRC105 (Anti-Endoglin Antibody) in Adults With Advanced/Metastatic Urothelial Carcinoma

Abstract: Although TRC105 was well tolerated, it did not improve 6-month PFS in heavily pretreated patients with advanced UC. CD105 staining was present in 50% of UC tumors at different intensities. Our observations on the pharmacodynamic significance of immune subsets, CECs, and CTCs warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…TRC105 is a chimeric IgG1 antibody that binds human endoglin and murine endoglin, albeit with lower affinity, and is in development as an antiangiogenic therapy (3740). Because we have determined that endoglin promotes VEGF signaling and VEGF‐induced sprouting and angiogenesis, we asked whether TRC105 cooperates with anti–VEGF therapy to inhibit angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…TRC105 is a chimeric IgG1 antibody that binds human endoglin and murine endoglin, albeit with lower affinity, and is in development as an antiangiogenic therapy (3740). Because we have determined that endoglin promotes VEGF signaling and VEGF‐induced sprouting and angiogenesis, we asked whether TRC105 cooperates with anti–VEGF therapy to inhibit angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…This is underscored by the fact that phase 1 and 2 trials of TRC105 in solid tumors have shown it to be well tolerated at clinically relevant doses. [8][9][10] When the maximum tolerated dose was exceeded, at 15 mg/kg every week, hypoproliferative anemia has been reported. 9 This side effect was easily monitorable, reversible, and treatable without adverse sequelae, 9 however, this would be important to monitor closely in leukemia patients receiving TRC105.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] This receptor is a therapeutic target and TRC105, an endoglinneutralizing antibody, is currently in phase 2 and 3 trials as an antiangiogenic agent for the treatment of solid tumors. [8][9][10] In addition to the endothelial lineage, endoglin also plays a key role in hematopoiesis. We have reported an important function for endoglin in cell fate specification and early hematopoiesis, [11][12][13][14][15] and a potential role beyond the embryonic stage is suggested by the expression of this receptor on the hematopoietic stem cell (HSC) isolated from every hematopoietic site, including the aorta-gonad-mesonephros, 16,17 the fetal liver, 18 and the bone marrow (BM), 19,20 in which endoglin has been reported to identify the long-term repopulating HSC.…”
Section: Introductionmentioning
confidence: 99%
“…3234 More importantly, various studies have confirmed that, in more than ten solid tumor types, high expression of CD105 is correlated with poor patient outcomes, which makes it a widely-applicable target in cancer. 35–38 Using TRC105 (a chimeric IgG1 monoclonal antibody which binds to both human and murine CD105 39,40 ) as the targeting ligand, our group has monitored CD105 expression using both antibody and nanoplatforms, demonstrating the great potential of CD105-targeted agents for future extensive applications in cancer diagnosis and therapy. 41–47 Inspired by this previous success, we set out to develop our first PET/MRI probe targeted to CD105.…”
Section: Introductionmentioning
confidence: 99%